2009
DOI: 10.1080/09652540903216254
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising and measuring defensive marketing orientation (DMO): some inaugural thoughts on assessing marketing's place in ‘society's doghouse’

Abstract: Many commentators suggest that marketing should be at the heart of strategic decision making, yet lament its continued inability to establish a presence at business"s top table. Such failure is generally deemed to be the fault of the organization at large, and there is a generally implied presumption that marketers are unfairly marginalized. For marketing to succeed, however, it must be perceived as both credible and contemporary, yet there are small, though substantive, bodies of research implying, 1) that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Most researchers perceive that recognition of customer needs and expectations is the main component of marketing orientation (Kobylanski and Szulc, 2011). Chiou and Chang (2009); Woodalla and Swailes (2009) and Avlonitis and Gounaris (1999) defined the concept of marketing orientation as the degree to which an organization obtains and uses information from customers, develops a strategy which will meet customer needs and implement that strategy by being responsive to customer needs and wants. Further, according to Kobylanski and Szulc (2011), it is the internal driving force that affects marketing actions, influence employees of an organization and their relationship with the customers.…”
Section: Marketing Orientationmentioning
confidence: 99%
“…Most researchers perceive that recognition of customer needs and expectations is the main component of marketing orientation (Kobylanski and Szulc, 2011). Chiou and Chang (2009); Woodalla and Swailes (2009) and Avlonitis and Gounaris (1999) defined the concept of marketing orientation as the degree to which an organization obtains and uses information from customers, develops a strategy which will meet customer needs and implement that strategy by being responsive to customer needs and wants. Further, according to Kobylanski and Szulc (2011), it is the internal driving force that affects marketing actions, influence employees of an organization and their relationship with the customers.…”
Section: Marketing Orientationmentioning
confidence: 99%
“…Both in this paper, though, and in Woodall and Swailes (2009), it has been suggested that we know little about how marketing managers view their responsibilities to the customer; to society; to the long-run success of the wider economy; and to theoretically optimizing organizational strategies. We do, though, know much about the customer -how he/she is likely to think and act, and how personalities, proclivities and vulnerabilities might best be manipulated to the organization's advantage.…”
Section: The 'New' Marketer/conclusionmentioning
confidence: 86%
“…The literature associating marketing and ethics is substantial (for a review see Schlegelmilch and Ö berseder, 2010) but the link between the practising marketer and marketing practice is rarely explored. Yet we are presently at a point of unique circumstantial convergence, where an interest in business ethics; damning evidence of continuing marketer indulgence; and calls for marketing to adopt a more defensive (Woodall, 2004;Woodall and Swailes, 2009), advocatory (Lawer and Knox, 2006;Urban, 2005), promise keeping (Grönroos, 2006), virtue-based (Murphy et al, 2007), matriarchal (Scott and Peñaloza, 2006), even humble (Cova, 2005), approach, have combined to identify the need for a different type of marketer -one that is holistically and intuitively suited to the demands of a different type of marketing, where individual values, attitudes and ethics are likely to be as important, if not more, than the ability to plan and execute a promotional campaign. The age of service (Vargo and Lusch, 2008), customer experience (Berry et al, 2002) and word of mouth (Kumar et al, 2007) is clearly upon us, yet there is a sense that marketers are struggling to understand how performance, rather than persuasion and a larger-than-life espousal of the possible, will win out in the longer term.…”
Section: A Shifting Marketing Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…There is no specific and common definition of MO. Some researches defined MO as the extent by which an organization receive and utilized information from clients, and constructs and carry out the implementation of a strategy that will fulfill the expectation of customer needs and wants (Chiou & Chang, 2009;Woodalla &Swailes, 2009 and. MO has been seen as the internal energy that will energize marketing implementation, and further effect the organization staff and their connection with the clients (Kobylanski & Szulc, 2011).…”
Section: Market Orientation (Mo)mentioning
confidence: 99%